The Impacts of Liberal Arts Education of Jesuit School Culture on English Teachers’ Transformed Agencies - Sutono, Aditya Agung; Budiraharjo, Markus (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2020)
Teachers as agents of change play a key role to not only assist their students with their learning, but also to professionally navigate the tension among their own beliefs, school culture, and the mandated curriculum. Drawing upon principles of Liberal Arts Education, a Jesuit Senior High School in Yogyakarta has carried out liberal arts education (LAE) since its inception in 1948, so as to nurture students’ capability to make their own choices and become responsible to their own deeds. This study is set to 1) discover transformative processes of four English teachers in their efforts to adopt and adapt to existing school values, and 2) elaborate the ways in which these teachers adopted and implemented the LAE and Ignatian Pedagogy into their teaching activities. This research employs Narrative Inquiry for its research method. Data gathering was accomplished by interviews, school observations, field notes, and document analysis. Four English teachers and some students were involved in the interviews. To guide data analysis, Mezirow’s (1998) Critical Self-Reflection of Assumptions (CSRA) and Biesta, Priestly, Robinson’s (2015) teacher agency were utilized. Findings suggest that transformed agencies took place in response to catalytic moments, especially due to the changing nature of students and the expectation to maintain quality teaching. Further studies may address a larger scope of teacher agencies among teachers in public schools.